1992
DOI: 10.1029/92ja01842
|View full text |Cite
|
Sign up to set email alerts
|

Mirror and ion cyclotron anisotropy instabilities in the magnetosheath

Abstract: Magnetosheath plasmas are typically characterized by a proton/• > 1 and a proton temperature anisotropy V.l_/T]l > 1. Such a plasma is unstable to both the ion cyclotron anisotropy and mirror instabilities, and evidence for both of these growing modes has been found in the magnetosheath. In this paper, we use one-dimensional hybrid simulations to investi•[ate the kinetic properties of these two instabilities. We find that, for moderate values of ion/• and temperature anisotropy, the two instabilities produce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 29 publications
(19 reference statements)
2
56
1
Order By: Relevance
“…A possible explanation is that because ion-cyclotron waves have phase velocities much greater than the mirror-mode waves, we are not able to observe them in the same region where MMSs are present because they might have left the region of observation. That both waves are cogenerated even when their growth rates are very different was shown observationally by Russell et al [2006] for the low beta conditions in the Saturnian magnetosphere and has also been observed in simulations [McKean et al, 1992[McKean et al, , 1994.…”
Section: Discussionmentioning
confidence: 89%
“…A possible explanation is that because ion-cyclotron waves have phase velocities much greater than the mirror-mode waves, we are not able to observe them in the same region where MMSs are present because they might have left the region of observation. That both waves are cogenerated even when their growth rates are very different was shown observationally by Russell et al [2006] for the low beta conditions in the Saturnian magnetosphere and has also been observed in simulations [McKean et al, 1992[McKean et al, , 1994.…”
Section: Discussionmentioning
confidence: 89%
“…Recent attempts to illustrate the role of the Alfve´n/ioncyclotron modes in the magnetosheath have stressed the mode's ability to pitch-angle scatter particles, as revealed by one-and two-dimensional hybrid simulations (McKean et al, 1992b;Gary and Winske, 1993;Gary et al, 1993c;McKean et al, 1994). This scattering thereby results in a more-thermalized equilibrium state Denton et al, 1994b;Gary and Lee, 1994;Gary et al, 1993a;Gary et al, 1994a;Gary et al, 1994b;Gary et al, 1994c).…”
Section: Alfve´n/ion-cyclotron Wavesmentioning
confidence: 99%
“…Resonant interactions, i.e., cyclotron resonance with plasma particles, are therefore expected to be effective in the relaxation of temperature anisotropy in this case. The interest to explain these effects and their consequences in the solar wind has been boosted after the simulations suggested that the mirror instability is not an effective pitch angle scatterer of protons (McKean et al 1992Gary et al 1993.a) and the cyclotron anisotropy instability may be assumed the primary mechanism to constrain the proton anisotropy (Gary and Lee 1994.a). Further confirmation of this constraint can also be obtained in a straightforward way, namely, by fitting the instability thresholds predicted by the linear theory with the anisotropy limits reported by the observations (see explanatory arguments and references in Gary et al (1994.b)).…”
Section: Introductionmentioning
confidence: 99%